More food, but less land and water for nature: why agricultural productivity gains did not materialize - Seijger, C.; Urfels, A.; Christoforidou, M.; Hellegers, P.; Borghuis, G.; Langan, Simon; van Halsema, G. (Elsevier, 2025)
Realism about productivity gains in agriculture and water is critical to understand if the world can feed itself while protecting nature. We use government-reported data to review progress over 2000–2020 compared to projections for irrigated and rainfed agriculture and trade. Our results over the period 2000–2020 show that productivity gains largely did not materialize. Instead of consolidating cereal production and trade in favourable regions like North America, Europe and Russia, their arable land declined by 35 million hectares, while arable land expanded by 74 million hectares in Africa, Latin America and Eastern Asia. Likewise, water productivity gains did not materialize, as photosynthesis breakthroughs did not occur. Land productivity (yield) gains were projected to rise 21–61 %, making the observed increase in cereal yields of 31 % a slight one. This puts the world on the path of using steadily more land and water to produce food and feed, at the expense of nature. Solutions to veer off this path include reducing food demand (including dietary change), stabilising rainfed agriculture and broadening the crop genetic resources base.